Posybilizm metafzyczny w filmie i serialu najnowszym - Biedny, Jan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article focuses on the reading of Waldemar Frąc’s film theory in the context of the newest film examples. In the first part, the author presents the most important features of the “possible cinema” and expands it with a philosophical possible worlds theory, and also gives the context of mind-game films. In the second part, the author proposes an interpretation of two films: Annihilation and Arrival, and the Dark series in the face of the presented theoretical solutions. The main point of the analysis is to show how the worlds presented in the given films exist, how the concept of possibility/the possible world is manifested, and what changes occur at the level of the film narrative itself. Interpretation of the film examples leads the author to the conclusion that metaphysical possibilism in the film and series reveals not only ontological themes, but also has significant intercultural value and moves existential reflection.